The Grimké sisters from South Carolina : pioneers for women's rights and abolition - Lerner, Gerda, 1920-2013 (The University of North Carolina Press, 2004)
"A landmark work of women's history originally published in 1967, Gerda Lerner's best-selling biography of Sarah and Angelina Grimke explores the lives and ideas of the only southern women to become antislavery agents in the North and pioneers for women's rights. This revised and expanded edition includes two new primary documents and an additional essay by Lerner. In a revised introduction Lerner reinterprets her own work nearly forty years later and gives new recognition to the major significance of Sarah Grimke's feminist writings."--Jacket.